Keanekaragaman Herba di Kawasan Aliran Air Panas Jaboi Kecamatan Sukajaya Sabang - Muhammad Zulian Iqbal; Muslich Hidayat; Safrul Mulyadi; Cut Ratna Dewi; Eriawati Eriawati; Nurlia Zahara (Lembaga Pengembangan Kinerja Dosen, 2025)
Herbaceous plants play an important role in reducing the negative impact of erosion on the surrounding environment. Their high adaptability and solitary distribution patterns allow herbs to grow in various habitat conditions. One location that shows a fairly high diversity of herbs is in the Jaboi Hot Spring Area, Sukajaya District, Sabang City. This study focused on grouping the types of herbaceous plants in the area and assessing their diversity. Data collection was carried out using a 100-meter line transect method, which was divided into four observation stations. Each station consisted of six 2 x 2-meter square plots used for species inventory. The observation resulted in data on 22 identified herbaceous species, representing 13 families, with a total of 385 individuals. The Convolvulaceae and Fabaceae families were the most dominant groups with four species from each family. The level of species diversity was analyzed using the Shannon-Wiener index, resulting in a score of 2.82, which is classified as moderate. The findings of this study provide preliminary information on the diversity of herbaceous plants in the area, which can be used as a reference for further research and environmental management in the Jaboi Hot Spring Area, Sukajaya District, Sabang City.